Columnar honeycomb structure

JP2026166778APending Publication Date: 2026-10-14NGK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025059952
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0013】 本発明の一実施形態によれば、高気孔率でありながら、触媒の隔壁内部への浸み込みを効果的に抑制できる柱体状ハニカム構造体が提供される。これにより、例えば、当該柱体状ハニカム構造体を触媒担体として使用することで、触媒温度を活性化温度まで短時間で上昇する機能を発揮できるようになる。また、隔壁に担持した触媒は隔壁内部に浸み込みにくいので、触媒を効率的に利用することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166778000001_ABST
    Figure 2026166778000001_ABST
Patent Text Reader

Abstract

The present invention provides a columnar honeycomb structure that has high porosity while effectively suppressing the penetration of catalysts into the interior of the partition walls. [Solution] A columnar honeycomb structure comprising an outer peripheral wall and a plurality of partition walls disposed on the inner peripheral side of the outer peripheral wall, penetrating from a first bottom surface to a second bottom surface, and forming a flow channel having openings at both ends, wherein the average porosity of the plurality of partition walls, measured according to the mercury intrusion method specified in JIS R1655:2003, is 50-60%, and the ratio of the volume occupied by pores with a pore diameter of 6 μm or more to the total pore volume of the plurality of partition walls, measured according to the mercury intrusion method specified in JIS R1655:2003, is 40% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a columnar honeycomb structure. In particular, this invention relates to a columnar honeycomb structure for exhaust gas purification. [Background technology]

[0002] Exhaust gases emitted from internal combustion engines, such as those found in automobiles, contain pollutants such as soot, nitrogen oxides (NOx), soluble organic components (SOF), hydrocarbons (HC), and carbon monoxide (CO). Therefore, it is common practice to purify exhaust gases by installing columnar honeycomb structures supported by appropriate catalysts (oxidation catalysts, reduction catalysts, three-way catalysts, etc.) depending on the pollutants in the exhaust gas system of internal combustion engines.

[0003] The columnar honeycomb structure comprises an outer peripheral wall and a plurality of porous partitions disposed on the inner periphery of the outer peripheral wall, which divide a plurality of cells that form a flow channel from the first bottom surface to the second bottom surface. A catalyst layer containing the above-mentioned catalyst can be formed on the surface of the porous partitions.

[0004] In recent years, development has progressed on columnar honeycomb structures that can quickly raise the temperature of the catalyst layer to its activation temperature after the engine has started. In order to raise the catalyst layer to its activation temperature in a short time, the columnar honeycomb structure needs to be made lighter. That is, the heat capacity of the partitions needs to be reduced by making them thinner or increasing their porosity. In this way, the partitions can be heated up quickly after the exhaust gas begins to flow, and the catalyst layer formed on the surface of the partitions can be heated up to its activation temperature in a short time. However, there is a limit to how thin the partitions can be, so increasing the porosity is one way to reduce weight. A concern in this case is that the strength of the columnar honeycomb structure may decrease.

[0005] Against this backdrop, Patent Document 1 describes an invention aimed at achieving practically satisfactory compressive strength characteristics despite the partition walls being thin, by satisfying the aforementioned certain conditions between the wall thickness of the partition and the opening ratio and / or bulk density of the honeycomb structure.

[0006] Furthermore, Patent Document 2 describes an invention aimed at providing a columnar honeycomb structure having a partition wall structure suitable for achieving both lightness and high strength by controlling the maximum and minimum values ​​when measuring the porosity in the thickness direction from one surface to the other surface of each partition wall using an X-ray microscope. Patent Document 2 also describes that the average pore diameter of the partition walls measured by a mercury porosimeter is 10 μm or less, that when measuring the porosity (%) in the thickness direction from one surface to the other surface of each partition wall, the average porosity of each partition wall is 40 to 70%, and that the difference between the maximum and minimum values ​​of porosity in each partition wall is 11% or less.

[0007] However, a problem arises when the average porosity is high, as the catalyst is more likely to seep into the partition walls during catalyst application. If the catalyst seeps into the cell walls, the exhaust gas and catalyst may not come into contact, potentially preventing the desired purification performance from being achieved. Therefore, Patent Document 3 describes an invention for partition walls constituting a columnar honeycomb structure, which aims to increase the average porosity for weight reduction while ensuring high strength and suppressing the seeping of the catalyst into the partition walls. This invention involves locally reducing the porosity of the partition wall surface, where stress is easily generated, and further reducing the average pore diameter. [Prior art documents] [Patent Documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 7-39761 [Patent Document 2] Japanese Patent Publication No. 2023-151174 [Patent Document 3] Japanese Patent Publication No. 2023-151167 [Overview of the project]

Problem to be Solved by the Invention

[0009] As described above, technological development has been carried out to achieve weight reduction and high strength of columnar honeycomb structures. Recently, in addition to these efforts, the problem of suppressing the penetration of catalyst into the interior of partition walls has also been added, increasing the difficulty of technological development for columnar honeycomb structures. The thinnest cell wall introduced to the market is 0.05 mm, and it is difficult to make the partition walls thinner than this, so weight reduction has to be achieved by increasing the porosity. For this reason, how to prevent the catalyst from penetrating into the partition walls while increasing the porosity has become a problem.

[0010] The invention described in Patent Document 3 also aims to improve the suppression of catalyst penetration into the interior of partition walls, but there is still room for improvement. In the invention described in Patent Document 3, the porosity within 5% of the thickness from the surface of the partition wall is reduced to suppress penetration, but the pore diameter that directly affects catalyst penetration has not been clarified. The present invention has been made in view of the above circumstances, and in one embodiment, an object of the present invention is to provide a columnar honeycomb structure that can effectively suppress the penetration of catalyst into the interior of partition walls while having high porosity.

Means for Solving the Problem

[0011] As a result of intensive studies by the present inventor to solve the above problems, regarding the partition walls constituting the columnar honeycomb structure, while increasing the average porosity for weight reduction, in order to suppress the penetration of catalyst into the interior of the partition walls, it was found that reducing the volume ratio of pores of 6 μm or more relative to the total pore volume of the partition walls is more important than controlling the average pore diameter. The present invention completed based on this finding is exemplified below.

[0012] [Aspect 1] A columnar honeycomb structure comprising an outer peripheral side wall, and a plurality of partition walls disposed on the inner peripheral side of the outer peripheral side wall, partitioning a plurality of cells that form flow paths penetrating from a first bottom surface to a second bottom surface and having openings at both ends, wherein The average porosity of the multiple partitions, as measured according to the mercury intrusion method specified in JIS R1655:2003, is 50-60%. The proportion of the total pore volume of the multiple partitions, measured according to the mercury intrusion method specified in JIS R1655:2003, that is occupied by pores with a diameter of 6 μm or larger is 40% or less. A columnar honeycomb structure. [Aspect 2] A columnar honeycomb structure according to Embodiment 1, wherein the proportion of the volume occupied by pores with a pore diameter of 6 to 7 μm relative to the total pore volume of the plurality of partitions, as measured according to the mercury intrusion method specified in JIS R1655:2003, is 10% or less. [Aspect 3] A columnar honeycomb structure according to embodiment 1 or 2, wherein the pore diameter (D50) at the time when mercury equivalent to 50% of the total pore volume of the plurality of partitions is injected by the mercury intrusion method specified in JIS R1655:2003 is 5.2 μm or less. [Aspect 4] A columnar honeycomb structure according to any one of embodiments 1 to 3, wherein the pore diameter (D10) at the time when mercury equivalent to 10% of the total pore volume of the plurality of partitions is injected by the mercury intrusion method specified in JIS R1655:2003 is 2.7 μm or less. [Aspect 5] A columnar honeycomb structure according to any one of embodiments 1 to 4, wherein the pore diameter (D90) at the time when mercury equivalent to 90% of the total pore volume of the plurality of partitions has been injected by the mercury intrusion method specified in JIS R1655:2003 is 13.1 μm or less. [Aspect 6] The pore diameter (D50) at the point when mercury equivalent to 50% of the total pore volume of the multiple partitions has been injected, as measured by the mercury intrusion method specified in JIS R1655:2003, is 5.2 μm or less. The pore diameter (D10) at the point when 10% of the total pore volume of the multiple partitions has been injected with mercury, as measured by the mercury intrusion method specified in JIS R1655:2003, is 2.7 μm or less. A columnar honeycomb structure according to embodiment 1 or 2, wherein the pore diameter (D90) at the time when mercury equivalent to 90% of the total pore volume of the plurality of partitions is injected by the mercury intrusion method specified in JIS R1655:2003 is 13.1 μm or less. [Aspect 7] A columnar honeycomb structure according to any one of claims 1 to 6, wherein, when measured by the mercury intrusion method specified in JIS R1655:2003, the pore volume occupied by pores with a pore diameter of 6 μm or more in the plurality of partitions is 0.14 cc / g or less. [Aspect 8] A columnar honeycomb structure according to any one of claims 1 to 7, wherein, when measured by the mercury intrusion method specified in JIS R1655:2003, the pore volume occupied by pores with a pore diameter of 6 to 7 μm in the plurality of partitions is 0.050 cc / g or less. [Aspect 9] A columnar honeycomb structure according to any one of embodiments 1 to 8, wherein the average thickness of the plurality of partitions is 50 to 150 μm. [Aspect 10] A columnar honeycomb structure according to any one of embodiments 1 to 9, wherein the plurality of partitions are formed of ceramics containing 90% by mass or more of cordierite. [Aspect 11] A columnar honeycomb structure according to any one of embodiments 1 to 10, wherein a catalyst layer is provided on the surface of the plurality of partition walls. [Effects of the Invention]

[0013] According to one embodiment of the present invention, a columnar honeycomb structure is provided that has high porosity while effectively suppressing the penetration of catalyst into the partition walls. As a result, for example, by using the columnar honeycomb structure as a catalyst support, the catalyst can be raised to its activation temperature in a short time. Furthermore, since the catalyst supported on the partition walls is less likely to penetrate into the partition walls, the catalyst can be utilized efficiently. [Brief explanation of the drawing]

[0014] [Figure 1] This is a schematic perspective view showing a columnar honeycomb molded body. [Figure 2] This is a schematic cross-sectional view of a columnar honeycomb structure observed from a direction perpendicular to the direction in which the cells extend. [Figure 3] This is a schematic magnified view of a columnar honeycomb structure observed in a cross-section perpendicular to the direction in which the cells extend. [Figure 4] This graph shows the correlation between the pore size of the partition wall and the effect of inhibiting catalyst penetration. [Modes for carrying out the invention]

[0015] Next, embodiments of the present invention will be described in detail with reference to the drawings. The present invention is not limited to the following embodiments, and it should be understood that appropriate design changes, improvements, etc., can be made based on the ordinary knowledge of those skilled in the art, without departing from the spirit of the invention.

[0016] <1. Columnar honeycomb structure> Figures 1 and 2 illustrate schematic perspective and cross-sectional views, respectively, of a columnar honeycomb structure 100 applicable as a catalyst carrier in an automotive exhaust gas purification system. This columnar honeycomb structure 100 comprises an outer peripheral side wall 102 and a plurality of partition walls 112 disposed on the inner circumferential side of the outer peripheral side wall 102, which penetrate from a first bottom surface 104 to a second bottom surface 106 and divide a plurality of cells 108 that form a flow path having openings at both ends. In this columnar honeycomb structure 100, exhaust gas flowing into one cell 108 from the first bottom surface 104 is purified as it passes through the cell and flows out from the second bottom surface 106.

[0017] There are no restrictions on the shape of the base of the columnar honeycomb structure 100, but it can be a round shape such as a circle, ellipse, racetrack shape, or oval shape, a polygonal shape such as a triangle or square shape, or other irregular shapes. The columnar honeycomb structure 100 shown in the figure has a circular base and is cylindrical overall.

[0018] There are no particular restrictions on the height of the columnar honeycomb structure (length from the first base to the second base), and it can be set appropriately according to the application and required performance. There are also no particular restrictions on the relationship between the height of the columnar honeycomb structure and the maximum diameter of each base (referring to the maximum length of the diameter passing through the centroid of each base of the columnar honeycomb structure). Therefore, the height of the columnar honeycomb structure may be longer than the maximum diameter of each base, or the height of the columnar honeycomb structure may be shorter than the maximum diameter of each base.

[0019] While not limited to specific materials, ceramics can be used as the materials constituting the partition walls and outer side walls of a columnar honeycomb structure. Examples of ceramics include cordierite, mullite, zirconium phosphate, aluminum titanate, silicon carbide (SiC), silicon-silicon carbide composites (e.g., Si-bonded SiC), cordierite-silicon carbide composites, zirconia, spinel, indialite, sapphirin, corundum, titania, and silicon nitride. These ceramics may be present individually or in combination of two or more.

[0020] In a preferred embodiment, the partition wall is formed of ceramics containing 90% by mass or more of cordierite. This means that the total mass percentage of cordierite (2MgO·2Al2O3·5SiO2) in 100% by mass of the material constituting the partition wall is 90% by mass or more. More preferably, the mass percentage of cordierite in 100% by mass of the material constituting the partition wall is 95% by mass or more, and even more preferably 99% by mass or more. It is also possible to remove unavoidable impurities and make 100% by mass of the material constituting the partition wall cordierite.

[0021] The cordierite content can be measured by X-ray diffraction. Specifically, using an X-ray diffractometer with Cu Kα rays (e.g., the X'pert PRO instrument from PANalytical), X-ray diffraction measurements are performed on the outer sidewall, partition, or sealing portion of the sample in the range of 2θ = 8 to 100°. The cordierite crystal phase ratio is then determined by analyzing the results using the Rietveld analysis program RIETAN, and this is defined as the cordierite content.

[0022] From the viewpoint of ensuring strength, the lower limit of the average thickness of the partition walls in the columnar honeycomb structure is preferably 50 μm or more, more preferably 60 μm or more, and even more preferably 70 μm or more. Furthermore, from the viewpoint of suppressing pressure loss, the upper limit of the average thickness of the partition walls is preferably 150 μm or less, more preferably 130 μm or less, and even more preferably 100 μm or less. Accordingly, the average thickness of the partition walls is preferably, for example, 50 to 150 μm, more preferably 60 to 130 μm, and even more preferably 70 to 100 μm. Figure 3 shows a schematic partial enlargement view of the partition wall 112 of the columnar honeycomb structure 100 when observed in a cross section perpendicular to the direction in which the cells 108 extend. In this specification, the thickness of the partition wall refers to the length D of the line segment that crosses the partition wall when the centroids C of adjacent cells are connected by a line segment L in a cross section perpendicular to the direction in which the cells extend (the height direction of the columnar honeycomb structure). The average thickness of a septum refers to the average thickness of all septums.

[0023] In a columnar honeycomb structure, the partitions can be porous. From the viewpoint of catalyst support, the lower limit of the average pore diameter of the partitions in the columnar honeycomb structure is preferably 3 μm or more. Furthermore, from the viewpoint of preventing catalyst penetration into the interior of the partitions, the upper limit of the average pore diameter of the partitions is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 6 μm or less. Therefore, the average pore diameter of the partitions is preferably, for example, 3 to 10 μm, more preferably 3 to 8 μm, and even more preferably 3 to 6 μm.

[0024] From the viewpoint of reducing weight and suppressing an increase in pressure loss, the lower limit of the average porosity of the partition wall is preferably 50% or more, and more preferably 54% or more. Furthermore, from the viewpoint of ensuring the strength of the columnar honeycomb structure, the upper limit of the average porosity of the partition wall is preferably 60% or less, and more preferably 56% or less. Therefore, the average porosity of the partition wall is preferably, for example, 50-60%, and more preferably 54-56%. In this specification, "porosity" is measured by the mercury intrusion method specified in JIS R1655:2003. The average porosity is measured as the average value obtained by taking partition wall samples (0.3g each) without bias from six locations in the columnar honeycomb structure and determining the porosity of each.

[0025] From the viewpoint of suppressing the penetration of the catalyst into the partition wall, it is effective to control the ratio of the volume occupied by pores with a diameter of 6 μm or more to the total pore volume of the partition wall. Specifically, the ratio of the volume occupied by pores with a diameter of 6 μm or more to the total pore volume of the partition wall, as measured according to the mercury intrusion method specified in JIS R1655:2003 (hereinafter also referred to as "volume ratio occupied by pores with a diameter of 6 μm or more") is preferably 40% or less, more preferably 30% or less, and even more preferably 20% or less. There is no particular lower limit set for the volume ratio occupied by pores with a diameter of 6 μm or more, but from the viewpoint of catalyst support, it is preferably 5% or more, and typically 10% or more. Therefore, the volume ratio occupied by pores with a diameter of 6 μm or more is preferably, for example, 5 to 40%, more preferably 5 to 30%, even more preferably 5 to 20%, and typically 10 to 40%.

[0026] Furthermore, the pore volume occupied by pores with a diameter of 6 μm or more within the multiple partitions is preferably 0.14 cc / g or less, more preferably 0.11 cc / g or less, and even more preferably 0.08 cc / g or less. Although no particular lower limit is set for the pore volume occupied by pores with a diameter of 6 μm or more within the multiple partitions, from the viewpoint of catalyst support, it is preferably 0.02 cc / g or more, and typically 0.04 cc / g or more. Therefore, the volume ratio occupied by pores with a diameter of 6 μm or more within the multiple partitions is preferably, for example, 0.02 to 0.14 cc / g, more preferably 0.04 to 0.11 cc / g, and even more preferably 0.04 to 0.08 cc / g. The volume ratio occupied by pores with a diameter of 6 μm or more is measured by the mercury intrusion method specified in JIS R1655:2003.

[0027] Even among pores with a diameter of 6 μm or more, the penetration of the catalyst into the partition wall can be effectively suppressed by controlling the ratio of the volume occupied by pores with a diameter of 6 to 7 μm to the total pore volume of the partition wall. Specifically, the ratio of the volume occupied by pores with a diameter of 6 to 7 μm to the total pore volume of the partition wall, as measured according to the mercury intrusion method specified in JIS R1655:2003 (hereinafter also referred to as "volume ratio occupied by pores with a diameter of 6 to 7 μm"), is preferably 10% or less, more preferably 8% or less, and even more preferably 6% or less. There is no particular lower limit set for the volume ratio occupied by pores with a diameter of 6 to 7 μm, but from the viewpoint of catalyst support, it is preferably 3% or more, and typically 4% or more. Therefore, the volume percentage occupied by pores with a diameter of 6-7 μm is preferably 3-10%, more preferably 3-8%, even more preferably 3-6%, and typically 4-10%.

[0028] Furthermore, the pore volume occupied by pores with a diameter of 6-7 μm within the multiple partitions is preferably 0.050 cc / g or less, more preferably 0.040 cc / g or less, and even more preferably 0.030 cc / g or less. While no particular lower limit is set for the pore volume occupied by pores with a diameter of 6-7 μm within the multiple partitions, from the viewpoint of catalyst support, it is preferably 0.005 cc / g or more, and typically 0.010 cc / g or more. Therefore, the volume ratio occupied by pores with a diameter of 6-7 μm within the multiple partitions is preferably, for example, 0.005-0.050 cc / g, more preferably 0.010-0.040 cc / g, and even more preferably 0.010-0.030 cc / g. The volume percentage occupied by pores with a diameter of 6-7 μm is measured by the mercury intrusion method specified in JIS R1655:2003.

[0029] Furthermore, in addition to controlling the volume ratio occupied by pores with a diameter of 6 μm or more and the volume ratio occupied by pores with a diameter of 6 to 7 μm, it is preferable to control the pore diameters D10, D50, and D90 of the septum.

[0030] Specifically, the pore diameter (D50) at the point when mercury equivalent to 50% of the total pore volume of the partition wall has been injected, as measured by the mercury intrusion method specified in JIS R1655:2003, is preferably 5.2 μm or less, more preferably 4.8 μm or less, and even more preferably 4.4 μm or less, from the viewpoint of preventing catalyst seepage into the interior of the partition wall. Furthermore, although no particular lower limit is set for D50, from the viewpoint of catalyst support, it is preferably 2 μm or more, and typically 4 μm or more. Therefore, D50 is preferably, for example, 2 to 5.2 μm, more preferably 2 to 4.8 μm, even more preferably 2 to 4.4 μm, and typically 4 to 5.2 μm.

[0031] The pore diameter (D10) at the point when 10% of the total pore volume of the partition wall has been injected using the mercury intrusion method specified in JIS R1655:2003 is preferably 2.7 μm or less, more preferably 2.5 μm or less, and even more preferably 2.3 μm or less, from the viewpoint of preventing catalyst seepage into the interior of the partition wall. Furthermore, although no particular lower limit is set for D10, from the viewpoint of catalyst support, it is preferably 1 μm or more, and typically 2 μm or more. Accordingly, D10 is preferably, for example, 1 to 2.7 μm, more preferably 1 to 2.5 μm, even more preferably 1 to 2.7 μm, and typically 2 to 2.7 μm.

[0032] The pore diameter (D90) at the point when 90% of the total pore volume of the partition wall has been injected using the mercury intrusion method specified in JIS R1655:2003 is preferably 13.1 μm or less, more preferably 10.6 μm or less, and even more preferably 8.1 μm or less, from the viewpoint of preventing catalyst seepage into the interior of the partition wall. Furthermore, although no particular lower limit is set for D90, it is preferably 7 μm or more from the viewpoint of catalyst support. Accordingly, D90 is preferably, for example, 7 to 13.1 μm, more preferably 7 to 10.6 μm, and even more preferably 7 to 8.1 μm.

[0033] The mercury intrusion method specified in JIS R1655:2003 involves immersing a sample in mercury under vacuum using a mercury porosimeter, applying uniform pressure, and gradually increasing the pressure while injecting mercury into the sample. The pore size distribution is then calculated from the pressure and the volume of mercury injected into the pores. As the pressure is gradually increased, mercury is injected into the pores starting with the largest diameters, increasing the cumulative volume of mercury. When all pores are finally filled with mercury, the cumulative volume reaches an equilibrium value. The cumulative volume at this point is the total pore volume (cm³). 3 The result is ( / g), and the pore diameters when 10%, 50%, and 90% of the total pore volume of mercury are injected are D10, D50, and D90, respectively. It is also possible to calculate the pore volume in a predetermined pore diameter range using a mercury porosimeter.

[0034] Six septum samples (0.3g each) were taken evenly from the columnar honeycomb structure, and the pore size distribution of each was measured. The volume percentage occupied by pores with a diameter of 6 μm or larger, the volume percentage occupied by pores with a diameter of 6 to 7 μm, D10, D50, and D90 were determined, and the average value was taken as the measured value.

[0035] There are no restrictions on the shape of the cell opening in a cross-section perpendicular to the direction in which the cell extends, but it is preferable that it be a square, hexagon, octagon, or a combination thereof. Among these, squares and hexagons are preferred. By shaping the cell opening in this way, the pressure loss when exhaust gas flows through the honeycomb structure is reduced. Furthermore, by shaping the cell opening in this way, the pressure loss when fluid flows through the columnar honeycomb structure is reduced, resulting in excellent catalytic purification performance.

[0036] There are no particular restrictions on the cell density (number of cells per unit cross-sectional area) in a columnar honeycomb structure; for example, 6 to 2000 cells / square inch (0.9 to 311 cells / cm²) is possible. 2 ), more preferably 50 to 1000 cells / square inch (7.8 to 155 cells / cm²). 2 ), particularly preferably 100 to 900 cells / square inch (15.5 to 139 cells / cm²). 2 ) can be expressed as follows. Here, the cell density is calculated by dividing the number of cells in the columnar honeycomb structure by the bottom area of ​​one side of the columnar honeycomb structure, excluding the outer perimeter side wall.

[0037] Referring again to Figure 3, when the columnar honeycomb structure 100 is used as a catalyst support, a catalyst layer 113 can be provided on the surface of the partition wall 112 according to the purpose. Examples of catalysts, though not limited to them, include oxidation catalysts (DOC) for increasing exhaust gas temperature by oxidative combustion of hydrocarbons (HC) and carbon monoxide (CO), PM combustion catalysts for assisting the combustion of PM such as soot, SCR catalysts and NSR catalysts for removing nitrogen oxides (NOx), and ternary catalysts capable of simultaneously removing hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (NOx). The catalyst may appropriately contain, for example, noble metals (Pt, Pd, Rh, etc.), alkali metals (Li, Na, K, Cs, etc.), alkaline earth metals (Mg, Ca, Ba, Sr, etc.), rare earth metals (Ce, Sm, Gd, Nd, Y, La, Pr, etc.), transition metals (Mn, Fe, Co, Ni, Cu, Zn, Sc, Ti, Zr, V, Cr, etc.).

[0038] <2. Method for manufacturing a columnar honeycomb structure> A method for manufacturing a columnar honeycomb structure is described below as an example. First, a raw material composition containing ceramic raw materials, a dispersion medium, a pore-forming material, and a binder is kneaded to prepare a clay body. Then, the clay body is extruded and dried to produce a columnar honeycomb molded body. Additives such as dispersants can be added to the raw material composition as needed. When extruding, a die having the desired overall shape, cell shape, partition wall thickness, cell density, etc., can be used.

[0039] In the drying process, conventional drying methods such as hot air drying, microwave drying, dielectric drying, reduced pressure drying, vacuum drying, and freeze-drying can be used. Among these, a drying method combining hot air drying with microwave drying or dielectric drying is preferred because it can dry the entire molded body quickly and uniformly. The pore seal portion can be formed by forming the pore seal portion at predetermined positions on both bottom surfaces of the dried honeycomb molded body and then drying the pore seal portion.

[0040] Ceramic raw materials are the materials that remain after firing metal oxides and metals, etc., and constitute the framework of the columnar honeycomb molded body (columnar honeycomb structure) after firing as ceramics. Ceramic raw materials can be provided, for example, in the form of powder. Examples of ceramic raw materials include materials for obtaining ceramics such as cordierite, mullite, zircon, aluminum titanate, silicon carbide, silicon nitride, zirconia, spinel, indialite, sapphirin, corundum, and titania. Specifically, although not limited to these examples, examples include silica, talc, alumina, kaolin, serpentine, pyroferrite, brucite, boehmite, mullite, magnesite, and aluminum hydroxide. Ceramic raw materials may be used individually or in combination of two or more types.

[0041] Cordierite can be suitably used as a ceramic material. In this case, a cordierite-forming raw material can be used as the ceramic raw material. A cordierite-forming raw material is a raw material that becomes cordierite upon firing. The cordierite-forming raw material preferably has a chemical composition of alumina (Al2O3) (including the portion of aluminum hydroxide that is converted to alumina): 30-45% by mass, magnesia (MgO): 11-17% by mass, and silica (SiO2): 42-57% by mass.

[0042] Examples of dispersion media include water, or a mixed solvent of water and an organic solvent such as alcohol, but water is particularly suitable.

[0043] The pore-forming material is not particularly limited as long as it becomes pore after firing, and examples include wheat flour, starch, foamed resin, superabsorbent resin, silica gel, carbon (e.g., graphite, coke), ceramic balloons, polyethylene, polystyrene, polypropylene, nylon, polyester, acrylic, phenol, etc. The pore-forming material may be used alone or in combination of two or more types. From the viewpoint of increasing the porosity of the honeycomb structure, the content of the pore-forming material is preferably 0.5 parts by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, per 100 parts by mass of ceramic raw material. From the viewpoint of ensuring the strength of the honeycomb structure, the content of the pore-forming material is preferably 12 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 7 parts by mass or less, per 100 parts by mass of ceramic raw material.

[0044] One method to reduce the proportion of the total pore volume of the partition wall occupied by pores with a diameter of 6 μm or more, and furthermore, the proportion of the volume occupied by pores with a diameter of 6 to 7 μm, is to adjust the size and amount of silica and pore-forming material added to the ceramic raw material. Specifically, it is preferable to satisfy the following three conditions. (Condition 1) The median diameter (D50) of the silica is greater than 5 μm and less than 10 μm. (Condition 2) The product of the median diameter of silica (μm) and the percentage of silica by mass per 100 parts by mass of ceramic raw material (%) must be greater than 100 (μm·%) and less than 200 (μm·%). (Condition 3) The value obtained by multiplying the square of the median diameter (μm) of the pore-forming material by the percentage (%) of the mass of the pore-forming material relative to 100 mass parts of the ceramic raw material is 1600 (μm). 2 Less than %) Here, the median diameter (D50) of silica and pore-forming material is a volume-based value measured by a laser diffraction / scattering particle size distribution analyzer.

[0045] When two or more types of silica and / or pore-forming materials are used, an average value is adopted for Condition 1. For Condition 2, the sum of the values determined for each silica is adopted. For Condition 3, the sum of the values determined for each pore-forming material is adopted. As an example, Condition 1, Condition 2 and Condition 3 in the case of using Silica A, Silica B, Pore-forming Material A, Pore-forming Material B, and Pore-forming Material C under the conditions described in Table 1 below are expressed by equations.

[0046] [Table 1]

[0047] (Condition 1) 10>{D50 (シリカA) ×INPUT (シリカA) +D50 (シリカB) ×INPUT (シリカB)} / {INPUT (シリカA) +INPUT (シリカB)}>5 (Condition 2) 200>D50 (シリカA) ×INPUT (シリカA) +D50 (シリカB) ×INPUT (シリカB) >100 (Condition 3) (D50 (造孔材A) ) 2 ×INPUT (造孔材A) +(D50 (造孔材B) ) 2 ×INPUT (造孔材B) +(D50 (造孔材C) ) 2 ×INPUT (造孔材C) <1600

[0048] In a preferred embodiment, the following Conditions 1a, 2a, and 3a are satisfied. (Condition 1a) The median diameter (D50) of silica is greater than 5 μm and less than 9 μm this (Condition 2a) The product of the median diameter of silica (μm) and the percentage of silica by mass per 100 parts by mass of ceramic raw material (%) must be greater than 100 (μm·%) and less than 180 (μm·%). (Condition 3a) The value obtained by multiplying the square of the median diameter (μm) of the pore-forming material by the percentage (%) of the pore-forming material's mass relative to 100 parts by mass of the ceramic raw material is 1500 (μm). 2 Less than %)

[0049] In a more preferred embodiment, the following conditions 1b, 2b, and 3b are met. (Condition 1b) The median diameter (D50) of the silica is greater than 5 μm and less than 8 μm. thing (Condition 2b) The product of the median diameter of silica (μm) and the percentage of silica by mass per 100 parts by mass of ceramic raw material (%) is greater than 100 (μm·%) and less than 160 (μm·%). (Condition 3b) The value obtained by multiplying the square of the median diameter (μm) of the pore-forming material by the percentage (%) of the pore-forming material's mass relative to 100 parts by mass of the ceramic raw material is 1400 (μm). 2 Less than %)

[0050] Examples of binders include organic binders such as methylcellulose, hydroxypropyl methylcellulose, hydroxyethylcellulose, carboxymethylcellulose, and polyvinyl alcohol. In particular, the combined use of methylcellulose and hydroxypropyl methylcellulose is preferred. Furthermore, from the viewpoint of increasing the strength of the honeycomb molded body before firing, the binder content is preferably 4 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 6 parts by mass or more, per 100 parts by mass of ceramic raw material. From the viewpoint of suppressing cracking due to abnormal heat generation during the firing process, the binder content is preferably 9 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 7 parts by mass or less, per 100 parts by mass of ceramic raw material. The binder may be used alone or in combination of two or more types.

[0051] Dispersants such as ethylene glycol, dextrin, fatty acid soap, and polyether polyol can be used. The dispersant may be used individually or in combination of two or more types. The dispersant content is preferably 0 to 2 parts by mass per 100 parts by mass of ceramic raw material.

[0052] A columnar honeycomb structure can be manufactured by performing a degreasing process and a firing process on a dried columnar honeycomb molded body. The conditions for the degreasing and firing processes can be those known according to the material composition of the honeycomb molded body and do not require special explanation, but specific examples of conditions are given below.

[0053] The degreasing process will now be explained. The combustion temperature of the binder is approximately 200°C, and the combustion temperature of the porosity-forming material is approximately 300-1000°C. Therefore, the degreasing process should be carried out by heating the honeycomb molded body to a temperature range of approximately 200-1000°C. The heating time is not particularly limited, but it is usually around 10-100 hours. The honeycomb molded body after the degreasing process is called a calcined body.

[0054] The firing process depends on the material composition of the honeycomb molded body, but for example, it can be carried out by heating the calcined body to 1350-1600°C in an atmospheric environment and holding it for 3-10 hours. [Examples]

[0055] (1. Manufacturing of honeycomb structures: Test numbers 1-16) Depending on the test number, the cordierite-forming raw materials, pore-forming materials A, B, C, binder, dispersant, and dispersion medium were added in the proportions shown in Table 2, mixed, and kneaded to prepare the clay. Talc, kaolin, alumina, aluminum hydroxide, and silica A and silica B were used as the cordierite-forming raw materials. Silica A and silica B have different median diameters (D50). Pore-forming materials A, B, and C also have different median diameters (D50). Water was used as the dispersion medium, a polyacrylic acid-based polymer was used as the pore-forming material, hydroxypropyl methylcellulose was used as the binder, and fatty acid soap was used as the dispersant. Furthermore, the median diameters (D50) of each material listed in Table 2 are volume-based values ​​measured using a laser diffraction / scattering particle size distribution analyzer (model LA960, manufactured by Horiba, Ltd.).

[0056] Table 2 shows the values ​​for silica A, silica B, pore-forming material A, pore-forming material B, and pore-forming material C using the following three formulas. Formula 1:{D50 (シリカA) ×INPUT (シリカA) +D50 (シリカB) ×INPUT (シリカB)} / {INPUT (シリカA) +INPUT (シリカB)} Formula 2: D50 (シリカA) ×INPUT (シリカA) +D50 (シリカB) ×INPUT (シリカB) Formula 3:(D50 (造孔材A) ) 2 ×INPUT (造孔材A) +(D50 (造孔材B) ) 2 ×INPUT (造孔材B) +(D50 (造孔材C) )2 ×INPUT (造孔材C)

[0057] This clay was fed into an extrusion molding machine and extruded horizontally through a predetermined die to obtain a cylindrical honeycomb molded body. After dielectric drying and hot air drying of the obtained honeycomb molded body, both bottom surfaces were cut to the predetermined dimensions to obtain a cylindrical honeycomb molded body.

[0058] The obtained cylindrical honeycomb molded bodies were degreased by heating at 200°C for 8 hours in an air atmosphere, and then fired at 1430°C for 4 hours in an air atmosphere to obtain columnar honeycomb structures. The number of columnar honeycomb structures required for each test example were manufactured. The specifications of the obtained columnar honeycomb structures are as follows. Overall shape: Cylindrical shape with a diameter of 118.4 mm and a height of 112.0 mm. Cell shape in a cross-section perpendicular to the flow direction of the cell: square Cell density (number of cells per unit cross-sectional area): 900 cells / cm³ 2 Average partition thickness: 64 μm (nominal value based on nozzle specifications) Cordierite content: 90% by mass or more

[0059] (2. Characteristic Evaluation) Various characteristics were evaluated for each of the honeycomb structures obtained above.

[0060] [2-1. Pore characteristics of the septum] The average porosity and pore size distribution of the septum were measured using a Micrometrics Autopore 9505 according to the measurement method described above. The results are shown in Table 2.

[0061] [2-2. Evaluation of catalyst penetration suppression effect] The catalyst penetration suppression effect was evaluated using the following procedure. First, a catalyst slurry containing an alumina-ceria-zirconia composite oxide with a median diameter of 3-7 μm was prepared. The catalyst was loaded onto a honeycomb structure using a wash coat method, where the catalyst slurry was introduced from the upper end face of the honeycomb structure and sucked from the lower end face. A predetermined amount of catalyst (170 g per liter of the external dimensions of the honeycomb structure) was loaded onto the partition walls of the honeycomb structure. Subsequently, the honeycomb filter loaded with the catalyst was hot-air dried at 120°C, and then subjected to heat treatment at 550°C for 1 hour to obtain a catalyst-supported honeycomb structure.

[0062] Two septum samples were taken from the central part of the catalyst-coated honeycomb structure, and the cross-section of the straight section perpendicular to the direction of cell extension (hatched area in Figure 3) was observed at 250x magnification using a scanning electron microscope (SEM). The obtained SEM images were analyzed using Winroof2018Standard ver4.0.1 image analysis software to determine the area of ​​the catalyst and substrate based on the intensity of the colors. The catalyst penetration rate was calculated as follows: Catalyst penetration rate = Area of ​​catalyst penetration into the septum / (Area of ​​catalyst penetration into the septum + Area of ​​catalyst covering the septum) × 100 (%). The average value of the measurements taken for the two samples was used as the measured value. The results are shown in Table 2.

[0063] [Table 2]

[0064] (3. Consideration) Comparing test numbers 1-12 and 16, which have a porosity of approximately 55%, it can be seen that the catalyst penetration rate in example test numbers 1-8 is significantly lower than that in comparative example test numbers 9-12 and 16. Although comparative example test numbers 13-15 have a low catalyst penetration rate, their low porosity prevents them from achieving both low catalyst penetration and weight reduction.

[0065] Based on the above test results, Figure 4 shows the results of investigating the correlation with the catalyst penetration inhibition effect by dividing the pore size into 1 μm intervals within the range of 0 to 10 μm. From Figure 4, it can be seen that the correlation coefficient increases significantly when the pore size is 6 μm or larger. In other words, it can be seen that controlling the proportion of volume occupied by pores with a diameter of 6 μm or larger is important for inhibiting catalyst penetration. [Explanation of Symbols]

[0066] 100: Columnar honeycomb structure 102: Outer perimeter side wall 104: First bottom surface 106:Second bottom surface 108: Cell 112: Bulkhead 113: Catalyst layer

Claims

1. A columnar honeycomb structure comprising an outer peripheral wall and a plurality of partition walls disposed on the inner peripheral side of the outer peripheral wall, penetrating from a first bottom surface to a second bottom surface, and dividing a plurality of cells that form a flow channel having openings at both ends, The average porosity of the multiple partitions, as measured according to the mercury intrusion method specified in JIS R1655:2003, is 50-60%. The proportion of the volume occupied by pores with a diameter of 6 μm or larger relative to the total pore volume of the multiple partitions, as measured according to the mercury intrusion method specified in JIS R1655:2003, is 40% or less. A columnar honeycomb structure.

2. The columnar honeycomb structure according to claim 1, wherein the ratio of the volume occupied by pores with a pore diameter of 6 to 7 μm to the total pore volume of the plurality of partitions, as measured according to the mercury intrusion method specified in JIS R1655:2003, is 10% or less.

3. A columnar honeycomb structure according to claim 1 or 2, wherein the pore diameter (D50) at the time when mercury equivalent to 50% of the total pore volume of the plurality of partitions is injected by the mercury intrusion method specified in JIS R1655:2003 is 5.2 μm or less.

4. The columnar honeycomb structure according to claim 1 or 2, wherein the pore diameter (D10) at the time when mercury equivalent to 10% of the total pore volume of the plurality of partitions is injected by the mercury intrusion method specified in JIS R1655:2003 is 2.7 μm or less.

5. A columnar honeycomb structure according to claim 1 or 2, wherein the pore diameter (D90) at the time when mercury equivalent to 90% of the total pore volume of the plurality of partitions has been injected by the mercury intrusion method specified in JIS R1655:2003 is 13.1 μm or less.

6. The pore diameter (D50) at the point when mercury equivalent to 50% of the total pore volume of the multiple partitions has been injected, as measured by the mercury intrusion method specified in JIS R1655:2003, is 5.2 μm or less. The pore diameter (D10) at the point when mercury equivalent to 10% of the total pore volume of the multiple partitions has been injected, as measured by the mercury intrusion method specified in JIS R1655:2003, is 2.7 μm or less. A columnar honeycomb structure according to claim 1 or 2, wherein the pore diameter (D90) at the time when mercury equivalent to 90% of the total pore volume of the plurality of partitions has been injected by the mercury intrusion method specified in JIS R1655:2003 is 13.1 μm or less.

7. The columnar honeycomb structure according to claim 1 or 2, wherein, when measured by the mercury intrusion method specified in JIS R1655:2003, the pore volume occupied by pores with a pore diameter of 6 μm or more in the plurality of partitions is 0.14 cc / g or less.

8. The columnar honeycomb structure according to claim 1 or 2, wherein, when measured by the mercury intrusion method specified in JIS R1655:2003, the pore volume occupied by pores with a pore diameter of 6 to 7 μm in the plurality of partitions is 0.050 cc / g or less.

9. The columnar honeycomb structure according to claim 1 or 2, wherein the average thickness of the plurality of partitions is 50 to 150 μm.

10. The columnar honeycomb structure according to claim 1 or 2, wherein the plurality of partitions are formed of ceramics containing 90% by mass or more of cordierite.

11. The columnar honeycomb structure according to claim 1 or 2, wherein a catalyst layer is provided on the surface of the plurality of partition walls.

Citation Information

Patent Citations

  • Ceramic honeycomb structure

    JP1995039761A

  • Pillar-shaped honeycomb structure

    JP2023151167A

  • Pillar-shaped honeycomb structure

    JP2023151174A